Observation of an alternate pathway in the deprotonation of an isobutylaminocyclotetraphosphazene - Balci, Ceylan Mutlu; Besli, Serap; Yüksel, Fatma; Allen, Christopher W. (Elsevier Science Bv, 2018)
The reaction of 2,6-dichloro-hexaphenoxycyclotetraphosphazene (1) with isobutylamine leads to 2-iso-butylamino-6-chloro-hexaphenoxycyclotetraphosphazene (2). Upon deprotonation, 1 a P4N5 bicyclic cyclophosphazene (3) is formed by an intramolecular ring closure reaction. This is in contrast to the reaction of primary amino-heptachlorotetraphosphazenes under identical conditions which provide a different class of fused rings via an intermolecular pathway. This new synthesis route allows for the synthesis of bicyclic compounds having a cavity structure. The products (2 and 3) were characterized by elemental analysis, mass spectrometry, and H-1 and P-31 NMR spectroscopy. The molecular structures of compounds 1 and 3 were determined by single crystal X-ray structural analysis.
Keywords: Bicyclic Phosphazenes; Crystal-Structure; Cyclotriphosphazene; Polyphosphazene; Chemistry